Celtic woman, a new journey [videorecording (DVD)] : live at Slane Castle, Ireland (EMI Manhattan, 2007)
Celtic Woman returns with a brand new concert special from the legendary Irish venue Slane Castle. A New Journey features the group's signature Celtic sound on both classic and contemporary songs.